Fermentation Strategy for Cutinase - Huang, Yan (Cutinase: Preparation and Application, 2021)
The fermentation conditions for the expression of cutinase by the mediation of pelB signal peptide have been optimized in this study, such as the concentration of the inducer isopropyl \(β\)-D-1-thiogalactopyranoside (IPTG) and the induction temperature, as well as the addition of glycine and surfactant sodium bodeoxycholate (TDOC). The highest activity of cutinase in the culture medium reached 149.2 U/mL. To enhance the extracellular expression of cutinase, the recombinant E. coli expression system was constructed using the codon-optimized cutinase gene. After that, the induction strategy was optimized in a 3-L fermentor. Results showed that the optimal induction condition was at a dry cell weight of 13.0 g/L, and the induction strategy was that IPTG is added once in a final concentration of 25.0 \(μ\)M, and lactose is fed at a rate of 0.5 g/L·h. In this condition, an extracellular cutinase activity of 2258.5 U/mL (5.1 g/L) was achieved, which was the highest cutinase production ever reported.